HtpG contributes to Salmonella Typhimurium intestinal persistence in pigs. (December 2015) - Verbrugghe, Elin; Van Parys, Alexander; Leyman, Bregje; Boyen, Filip; Haesebrouck, Freddy; Pasmans, Frank
Abstract Salmonella enterica subspeciesenterica serovar Typhimurium (Salmonella Typhimurium) contamination of pork, is one of the major sources of human salmonellosis. The bacterium is able to persist and hide in asymptomatic carrier animals, generating a reservoir forSalmonella transmission to other animals and humans. Mechanisms involved inSalmonella persistence in pigs remain poorly understood. In the present study, we demonstrate that theSalmonella htpG gene, encoding a homologue of the eukaryotic heat shock protein 90, contributes toSalmonella Typhimurium persistence in intestine-associated tissues of pigs, but not in the tonsils.HtpG does not seem to play an important role during the acute phase of infection. The contribution to persistence was shown to be associated withhtpG -dependentSalmonella invasion and survival in porcine enterocytes and macrophages. These results reveal the role of HtpG as a virulence factor contributing toSalmonella persistence in pigs.